Analysis of the Effect of Good Corporate Governance Implementation on Banking Financial Performance Measured Through the ROA & ROE Ratio in Sharia Commercial Banks in Indonesia - Prystina Ajeng Pratiwi (Perkumpulan Praktisi Akuntansi Indonesia, 2022)
The implementation of Good Corporate Governance for Islamic banking is regulated in PBI No. 11/33 / PBI / 2009 concerning the Implementation of Good Corporate Governance for Islamic Commercial Banks and Sharia Business Units. This study will show whether there is a relationship or influence from the implementation of GCG through several indicators such as the number of boards of directors, the board of commissioners, the number of meetings on the sharia supervisory board, and also the number of meetings of the audit committee at each Islamic commercial bank in Indonesia, with the dependent variable, namely financial performance as measured by Return on Assets (ROA) and Return on Equity (ROE). The number of research samples is from 10 Islamic commercial banks listed on the IDX for the period 2018-2019 with a purposive sampling technique. This study uses secondary data from annual reports and GCG implementation reports from each Islamic commercial bank. The analytical method used in this research is through hypothesis testing with regression analysis using the IBM SPSS V21. The test results found that simultaneously through the simultaneous F test, GCG has a positive effect on Return on Assets, and GCG simultaneously has no effect on Return on Equity.